PENGARUH KELOMPOK REFERENSI TERHADAP GAYA HIDUP DAN KEPUTUSAN PEMBELIAN HIJAB RABBANI KOTA PEKANBARU - Lisfah Asbi Syahfitri; Taufiqurrahman Taufiqurrahman; T. Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to find out how the influence of Reference Group on Lifestyle and Decision of Purchasing Hijab Rabbani in Pekanbaru. The population in this study is the consumer Hijab Rabbani in Pekanbaru in 2017. Sampling technique using purposive sampling to obtain the number of research samples as much as 100 respondents. Data analysis was done by path analysis processed with SPSS program version 18.0. From the results of tests that have been done is known that there is direct influence of the reference group on lifestyle and purchasing decisions. There is a direct influence of Lifestyle on purchasing decisions. And there is an indirect influence of the reference Group on the purchase decision of Hijab Rabbani in Pekanbaru which is a lifestylemediated one. It is expected to the company to see other opportunities that are not from friends or family of consumers because consumers in buying hijab not fully follow family and friends relatives and companies more convincing consumers with the quality of goods offered and affordable prices so that customers will have full interest in buying Hijab RabbaniKeywords : Reference Group, Lifestyle and Decision Purchasing